2022
DOI: 10.3390/jcm11216529
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Reticulohistiocytosis Associated with an Early Form of Systemic Lupus Erythematosus: A Case Report of a Rare Disease, with Mini Review of the Literature

Abstract: Multicentric reticulohistiocytosis (MRH) is the most frequently described form of reticulohistiocytosis (RH), and it is classified as a class IIb non-Langerhans cell histiocytosis. It has been designated as multicentric, being characterized by multisystemic involvement. In fact, although mainly involving the skin, along with the joints, it is a systemic inflammatory condition potentially involving every internal organ. As MRH-related skin findings can mimic rheumatoid nodules or Gottron papules, the histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 32 publications
0
12
0
5
Order By: Relevance
“…Reticulohistiocytosis comprises multicentric reticulohistiocytosis, generalized reticulohistiocytosis, and solitary reticulohistocytoma. Of all the three, MRH is the most common form of RH and is described in the literature as a class IIb non-Langerhans histiocytosis that frequently involves skin and joints [ 5 ]. Patients usually demonstrate symptoms and signs of symmetric polyarthritis and papulonodular cutaneous lesions (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reticulohistiocytosis comprises multicentric reticulohistiocytosis, generalized reticulohistiocytosis, and solitary reticulohistocytoma. Of all the three, MRH is the most common form of RH and is described in the literature as a class IIb non-Langerhans histiocytosis that frequently involves skin and joints [ 5 ]. Patients usually demonstrate symptoms and signs of symmetric polyarthritis and papulonodular cutaneous lesions (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These lesions often coalesce, giving a string of pearls or coral bead appearance. The joint involvement in MRH is quite destructive, and involvement of distal interphalangeal joints is typically seen in more than 75% of patients, which can be used as a distinguishing feature to differentiate from other erosive arthritis, such as rheumatoid arthritis [ 5 ]. In addition to skin and joints, multiple organs can be involved, such as the lung (pleural effusion, interstitial fibrosis, hilar lymphadenopathy), heart (pericardial effusion, myocarditis), gastrointestinal system, and urogenital system (genital tract and kidney) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarilumab and tocilizumab have been proposed as specific immunomodulators to treat MRH refractory patients based on the overexpression of IL-6 in the giant multinucleated cells of the MRH inflammatory infiltrate, which play a vital role in improving joints and dermatological manifestations. Meanwhile, a recent case report mentions that using anakinra (IL-1 inhibition) allowed for control of the disease[ 1 ]. In our patient, we initially treated with prednisone, hydroxychloroquine, leflunomide and MTX, but the patient failed to respond to MTX, with new nodules detected on her hands and feet after 6 mo of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CTX was of significant benefit in 20% of cases, with complete arthritis resolution, and in 27% of cases of skin lesions in MRH. Additionally, partial arthritis and skin disease control was seen in 40 and 45% of cases, respectively[ 1 ]. However, the precise mechanism of CTX was not documented, but it can be postulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation